An idea for education of corruption eradication in Indonesia: Five levels of corruption and their solutions - Hikmat, Hikmat (International Journal of Innovative Research and Scientific Studies, 2025)
The research investigated the extent and areas of massive corruption in almost all areas of the Indonesian government, across departments, levels of public office, and ministries. Indonesia's Corruption Perception Index (CPI) in 2022 scored 34, ranking 110 out of 180 countries, marking the worst decline since the reform era. The corruption involved 525 cases and 612 suspects, costing the country US$2.2 billion. Based on the descriptive analysis method, this study found that corruption occurs through five levels of areas, which I termed corruption by need, corruption by gate, corruption by read, corruption by lead, and corruption by meat. This new finding is expected to contribute to the sociology of corruption and anti-corruption education to address this severe problem through an educational model that should be organized in those five levels to achieve good governance and a clean government.